Gait Analysis after Unilateral Total Hip Replacement Surgery - Hamandi, Sadiq J.; Azzawi, Marwa; Abdulwahed, Waleed (Al-Nahrain Journal for Engineering Sciences, 2018)
Total hip replacement (THR) is an elective surgical procedure with the primary indication being pain relief. The aim of this study is to analyze gait dynamics for patients after they underwent a unilateral THR surgery and compare it with normal parameters. To investigate the gait dynamics a gait analysis was performed on five patients after they underwent a unilateral THR surgery; only two of them were examined before the surgery. The gait analysis was performed using a digital video camera with two force plates. Kinematics data were obtained from 2D trajectories of seven passive markers using SkillSpector software. MATLAB software has been used for inverse dynamics computation. General gait parameters, Harris Hip Score, joints’ angles, forces, moments and powers were obtained during gait cycle. It was found that the average of improvement in Harris Hip Score (for four patients who were examined 1.5, 2.5, 3 and 9 months after surgery) is 61.8 points, which is an indication of pain relief. In the other hand, the general gait parameters were found slightly lower than normal after THR surgery. The average hip reaction force was found to be 2.988 N/BW, which is within normal range. Also, the average of maximum hip extension and maximum hip flexion angles were found to be 25.69 and -13.524 degree respectively, which both are within normal ranges. Furthermore, hip, knee and ankle moments and powers results showed some abnormality. Therefore as a conclusion, patient satisfaction and functional improvement are not related to general gait parameter. And it is not unusual that gait mechanics improvement would not reach normal after months of recovery. Also, the results of gait dynamics which are from the engineer’s perspective are compatible with Harris Hip Score, which is from the physician’s perspective, in quantifying surgical results and subsequent recovery progress.